Wild Kratts. Wild animal babies [videorecording (DVD)] (PBS Distribution, 2016)
Explore nature, discover amazing animals, and meet wild animal babies with the Wild Kratts! Join Martin Kratt and Chris Kratt as they learn about the unique ways young animals are raised and protected by their parents. In select adventures on this DVD, the crew helps an adorable (and majorly destructive) baby elephant stay out of trouble, wrangles some playful lion cubs, and more! It's adventure at its most adorable!